(untitled) (Research, Society and Development, 2020)
Company goals can be achieved if a company has a good management, reputation, and effective communication within. Good company management does not merely happen within its internal scope, but it should be walked together with the external scope. Basically, company management wanted the company to run smoothly without any management crises. Public relation has very important role when the management crisis is experienced by a company. Hence, this research has objective to know the role of public relations in handling the crisis of dwelling time case in 2015. The methodology used in this research is qualitative methodology by using interview as the analyzing tool. The result showed that public relation of the Ministry of Trade is good enough in running its role in handling the dwelling time case by connecting and clarifying the problem. Also, the public relation of the Ministry of Trade has been done an internal refinement by isolating the problems.